Advances in sensitivity-based nonlinear model predictive control and dynamic real-time optimization. (June 2015) - Biegler, L.T.; Yang, X.; Fischer, G.A.G.
Abstract : Highlights: Description of NLP solution and sensitivity based on interior point methods. Extension of NMPC to advanced step algorithms which reduce on-line computation by 2–3 orders of magnitude. Extension of NMPC over multiple sampling times and to handle economic stage costs. Survey of known nominal and robust stability properties. Large-scale process case studies to demonstrate NMPC and D-RTO. Abstract: Recent results in the development of efficient large-scale nonlinear programming (NLP) algorithms have led to fast, on-line realizations of optimization-based methods for nonlinear model predictive control (NMPC) and dynamic real-time optimization (D-RTO), with predictive nonlinear dynamic (e.g., first principle) models. For NMPC, optimization-based controllers are developed that lead to well-understood stability and robustness properties, even for large, complex plant models. The realization of NMPC requires the application of a fast NLP solver for time-critical, on-line optimization, as well as efficient NLP sensitivity tools that require 2–3 orders of magnitude less computation than the NLP solution. This leads to advanced step NMPC (asNMPC), which essentially eliminates computational delay. We also extend these capabilities to dynamic real-time optimization (D-RTO) with more general stage costs that are economically based. This overview also extends input to state stability (ISS) properties for asNMPC to handle active set changes, and also for D-RTO through convex regularizations. Two large scale distillation case studies, based on nonlinear first principle models, are presented that demonstrate the effectiveness of these approaches.